THE EFFECT OF MORAL REASONING ON ADOLESCENT DEVIANT BEHAVIOR: THE ROLE OF MALTREATMENT MODERATION - Titik Muti’ah; Zahran Nur Wicaksana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Adolescence is an important period in the development of moral reasoning that serves as the basis for behavioral decision-making, but the experience of maltreatment in parenting can increase the tendency for deviant behavior. This study aims to examine the influence of moral reasoning on adolescent deviant behavior and examine the role of maltreatment as a moderator variable in these relationships. The research uses a quantitative approach with a correlational design. The research subjects amounted to 222 students of SMK Tamansiswa Jetis Yogyakarta aged 15–19 years who were selected using cluster sampling techniques. Data analysis was carried out with the help of the Jamovi application version 2.7.12 at a significance level of 0.05. However, the results of the moderation test The results of the study showed that moral reasoning had a negative and significant effect on deviant behavior (p < 0.05), while maltreatment had a positive and significant effect on adolescent deviant behavior (p < 0.05). Simultaneously, moral reasoning and maltreatment were able to explain 49.9% of the variation in deviant behavior. However, the results of the moderation test showed that the interaction between moral reasoning and maltreatment did not have a significant effect on deviant behavior (p = 0.261 > 0.05). Thus, the first and second hypotheses are accepted, while the third hypothesis is rejected, so that maltreatment does not act as a moderator variable in the relationship between moral reasoning and deviant behavior, but rather as an independent predictor.